Prepared 13X Zeolite as a Promising Adsorbent for the Removal of Brilliant Blue Dye from Wastewater - Barno, Suondos K. A.; Mohamed, Haider J.; Saeed, Siham M.; Al-Ani, Mohammed J.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
The research discussed the possibility of adsorption of Brilliant Blue Dye (BBD) from wastewater using 13X zeolite adsorbent, which is considered a byproduct of the production process of potassium carbonate from Iraqi potash raw materials. The 13X zeolite adsorbent was prepared and characterized by X-ray diffraction that showed a clear match with the standard 13X zeolite. The crystallinity rate was 82.15% and the crystal zeolite size was 5.29 nm. The surface area and pore volume of the obtained 13X zeolite were estimated. The prepared 13X zeolite showed the ability to remove BBD contaminant from wastewater at concentrations 5 to 50 ppm and the removal reached 96.60% at the lower pollutant concentration. Adsorption measurements versus time showed 48.18% removal of the dye during just the first half-hour and the maximum removal closest to the removal at the equilibrium after one and half hour. Langmuir isotherm was described the adsorption equilibrium data with a maximum adsorption capacity of 93.46 mg/g and the kinetics data of the adsorption process was followed the pseudo-second-order.